#TITLE_ALTERNATIVE# - FITRI (NIM 30506004), NOOR
Elemental speciation is the main topic of research on analytical chemistry, particularly to attain some information related to behaviors and characteristics of elements, for instance; their mobility, function, occurrence, deficiency and toxicity. The elemental behaviors both in organism and ecological system are not only elucidated by determining a total amount of elements in suitable samples, but also by determining the pattern of elemental species. In turn, this will help in better understanding of the properties and influence of the element. Some elements with various patterns of chemical species are needed for plant growth and development, for examples; Mg and Ca frequently act as the major nutrients, whereas Mn, Zn and Mo are mostly needed to be micronutrients. The functions and roles of those elements in the plants are already well known, however, what and how the elemental species are not yet fully understood. On those reasons, the elemental speciation of Mg, Ca, Mn, Zn, Mo and Cd in phloem sap of castor bean (Ricinus communis L.) was studied. The elemental speciation was primarily emphasized on the differentiation and distribution of chemical species of major nutrients Mg and Ca, micronutrients Mn, Zn and Mo, as well as chemical species of heavy metal Cd in the phloem sap samples. This work was focused on the operational speciation analysis, defined as species characterization, depending on the selected analytical methods. The main separation method employed size exclusion chromatography (SEC), whereas the supporting separation method was performed using quantitative preparative native continuous polyacrylamide gel electrophoresis (QPNC PAGE). Bidimensional separation of Mo species was done by applying of both methods above. Additionally, bidimensional separation of Ca species in the first stage was used SEC, whereas in the second stage, the separation was conducted using capillary electrophoresis (CE). Selective detection of elements was performed by inductively coupled plasma quadrupole mass spectrometry (ICP-QMS). In particular, molybdenum (Mo) was selectively detected by electrospray ionization-mass spectrometry (ESI-MS). The distribution of Mg, Ca, Mn, Zn, Mo, and Cd species according to the differences of their relative molecular weights were identified by using SEC method. Two SEC columns were applied, namely Sephadex G-50 SF (700 mm x 24 mm) and sephadex G-25 M (28 mm x 9 mm). In accordance with 20 mM MES/1 mM NaN3 pH 8,0 and 20 mM NaCl/1 mM NaN3 pH 8,0 solutions were used as the mobile phase, respectively. The operational parameters of separation applied for the sephadex G-50 SF column were (i) eluent flow of 0.3 mL/min, (ii) fraction volume of 7.2 mL with the total of fraction of 95 (automatic running fractionation), (iii) UV detection wavelenght of 254 nm, and (iv) temperature of separation system at 4 degrees C, whereas the operational conditions of separation applied for the sephadex G-25 M column were (i) eluent flow of 0.3 mL/min, (ii) fraction volume ranging from 0.1 to 0.2 mL, (iii) total of fraction of 20-40 (manual running fractionation), and (iv) separation system at room temperature. In order to standardize the molecular weight range of the chromatographic separation, a mixture protein standard consisting of thyroglobulin (670 kDa), γ-globulin (158 kDa), ovalbumin (44 kDa), myoglobin (17 kDa), and Vitamin B12 (1,35 kDa) were employed on sephadex G-50 SF column. After separation using sephadex G-50 SF and sephadex G-25 M column, the detected species are consecutively written in notations of subscript A and subscript B. Subscript A1, A2, etc, denotes the subsequent species of the same metal on the basis of their subsequent relative molecular weight. Quantitative preparative native continuous polyacrylamide gel electrophoresis (QPNC PAGE) method was also utilized in this study. The application of this method was aimed to obtain the species elution profiles on the basis of the m/z differences of the species. The experimental operational conditions were: (i) continuous buffer system of 20 mM Tris-HCl/1 mM NaN3 pH 10, (ii) polyacrylamide polymerization degree of 4 %T / 2,67 % C, with a length of gel of 40 mm, and mobile phase of 20 mM MES/1 mM NaN3 pH 8,0, and (iii) temperature of analysis of 4 degrees C. The samples were fractionated on 74 fractions with each fraction volume of 5 mL (automatic fractionation by programming). The further separation of Ca species was carried out by means of capillary electrophoresis (CE). This separation is based on the distinction of their analyte mobility for a given electric field. The electric field was applied along capillary column at a high voltage (15-30 kV) on both positive and negative electrodes. The separation of analytes was a result of analyte movement under influences of electroosmosis and electrophoresis phenomena. To attain an optimal separation method, the composition and concentration of buffer, pH, used voltage and the usage of surfactant as a modifier of electroosmosis flow were optimized. Selective elements in phloem sap of castor bean and in fractions of SEC and QPNC PAGE were detected by using inductively coupled plasma quadrupole mass spectrometry (ICP-QMS). In this method, analytes were ionized in plasma to be a cation (M+), and its count was calculated by quadrupole mass spectrometry (QMS). The operational conditions applied in the analysis consist of (i) power of 880-1200 Watt, (ii) pulse and analog detector system, (iii) argon gas flow of 14 L/min, (iv) nebulizer argon gas flow of 0,9-0,98 L/min, (v) sample flow of 1,2 mL/min, (vi) peak hopping signal process, (vii) sweeps/reading of 35-40/3-5, (viii) replication of 5 times, (ix) sample flush of 45 seconds, (x) read delay of 15 seconds, (xi) wash time of 60 seconds, and (xii) internal standard of 10 μg/L In in HNO3 1 % (b/b). The interaction probability of metals and protein/polypeptide was tested by using proteinase K. Prior to and after destruction using proteinase K, phloem sap was fractionated by means of sephadex G-25 M column and the elements were selectively detected by ICP-QMS. The protein content of the fractions was determined by Bradford method. The metal elution profiles of fractions resulted before and after destruction using proteinase K are compared and interpreted if any probability of interaction between metals and protein/polypeptide. On the basis of UV absorption profiles of phloem sap on sephadex G-50 SF column, 6 (six) groups of UV active species were identified. The six groups of species consisting of 1 (one) group (group A) was detected at a high molecular weight area (> 44 kDa), whereas the other 5 (five) groups (group B, C, D, E and F) were detected at a low molecular weight area. After SEC fractionation, elution profiles of C (carbon), P (phospor) and S (sulphur) species show a differentiation of C, P and S compouds in phloem sap. On sephadex G-25 M column, two C species (CB1 and CB2), four P species (PB1, PB2, PB3, and PB4), seven S species (SB1, SB2, SB3, SB4, SB5, SB6, and SB7). Fractions in an elution area ranging from 0,5 to 1,5 mL are collected and further separated on sephadex G-50 SF column by using a similar mobile phase (20 mM NaCl/ 1 mM NaN3 pH 8,0). As a result, two C species (CA1 and CA2), four P species (PA1, PA2, PA3, and PA4) and eleven S species annotated as SA1 to SA11 were well detected. Differentiation and distribution of Mg, Ca, Mn, Zn, Mo, and Cd species in phloem sap of castor bean were also investigated on the basis of their elution profiles after SEC separation. On the sephadex G-50 SF column, three Mg species (MgA1, MgA2 and MgA3), three Ca species (CaA1, CaA2 and CaA3), three species of Mn (MnA1, MnA2, and MnA3), three Zn species (ZnA1, ZnA2 and ZnA3), as well as two Mo species (MoA1 and MoA2) and five Cd species (CdA1 -CdA5) were identified. The first species of all metals were observed at a void volume (> 44 kDa), which coincides with UV active absorption of phloem sap. The relative abundance of the first species varies from 0.01 % (Mg species) to 10.37 % (Cd species) compared to other species for each metals. The major species of metals with a highest relative abundance were detected at low molecular weight area (< 1350 Da). The major species are positively correlated to UV active absorption of phloem sap. The result of SEC separation on sephadex G-25 M column indicates the presence of three Mg species (MgB1, MgB2 and MgB3), three Zn species (ZnB1, ZnB2 and ZnB3), two Ca species (CaB1 and CaB2), two Mn species (MnB1 and MnB2), two Mo species (MoB1 and MoB2), and one Cd species (CdB1). The culture difference of castor bean did not influence the differentiation of metal species, but influencing the total amount of species. In an aeroponic culture, the total amounts of MnA2 and MoA2 species as well as all CdA species were greater than those in a soil culture. This suggests that Mn, Mo, and Cd metals in the aeroponic culture were optimally absorbed compared those in the soil culture. The results of separation using QPNC PAGE indicate that Mn and Mon species are successfully detected. Molybdenum species were detected at elution area of 35-80 mL, whereas Mn species were identified at elution area ranging from 90 to 170 mL. The separation of Mg, Ca, Zn, and Cd species by using QPNC PAGE was not really working optimally, which is shown by a gradational species elution profiles and a high detection of quantification of Mg, Ca, Zn and Cd. Study on interaction probability between metal species and protein/polypeptide indicates that the total concentration of MgB1, spesi CaB1, spesi MnB1, MoB1, and CdB1 species decreases significantly, whereas the total concentration for low molecular weight species of Mg, Ca, Mn, Mo and Cd increases after destructed by proteinase K. The decrease of MgB1, spesi CaB1, spesi MnB1, MoB1, and CdB1 species suggests that these species may interact with protein/polypeptide. In contrary, there are no differences of Zn elution profiles before and after destructed by proteinase K. This suggests that Zn may not bind with protein/polypeptide. The occurrence and stability of MoA2 species were proven by SEC dan QPNC PAGE. Phloem sap was initially separated by SEC on sephadex G-50 SF column. The SEC fraction containg a highest concentration of Mo (43/elution volume of 309,6 mL) was further separated using QPNC PAGE. Alternatively, the first stage of separation was done by QPNC PAGE and the QPNC PAGE fraction containing a highest concentration of Mo (10 fractions/elution volume of 50 mL) was furthermore separated using SEC on sephadex G-50 SF column. As a result, by means of SEC and QPNC PAGE methods, the occurrence and stability of Mo species were well detected quantitatively. This is supported by ESI-MS detection results, which indicates that the relative molecular weight of MoA2 was less than 1000 Da. In addition, further separation of CaB2 species using capillary electrophoresis (CE) was also performed. The optimal conditions of the separation method was obtained at (i) composition and concentration of background electrolit (BGE) of 10 mM Na2HPO4/ 10 mM NaH2PO4/0,5 mM CTAB, (ii) pH of 8.0, (iii) voltage of -20 kV, (iv) wavelenght of detection/reference of 214/500 nm, and (v) optimal temperature at 14degrees C. As a result, CaB2 species was successfully separated by identifying a total of 13 UV active species in less than 10 minutes. Differentiation and distribution of Mg, Ca, Mn, Zn, Mo, and Cd species in phloem sap of castor bean were successfully carried out by means of SEC, QPNC PAGE, and CE separation methods as well as modified ICP QMS technique for selective detection of elements. The advantages of the modified separation and detection methods are their ability in differentiating and detecting minor species at a minimal relative abundance of 0.01 % (MgA1) and a lowest mass in pikogram orde (50 pg for CdA1 species). The study on differentiation and distribution of Mg, Ca, Mn, Zn, Mo, and Cd species could be a significant scientific contribution and undoubtedly benefited for a better understanding of mechanism of transformation and transport processes of those species in phloem sap of castor bean.